Bridging Technology and Morality: Faith-based Digital Creativity Model for Sustainable Vocational Education - Sari, Puji Novita; Yani, Ni Luh Sinta (Proceeding International Conference on Religion, Science and Education, 2026)
The advancement of digital technology has transformed learning in vocational education, encouraging students to express creativity through various platforms. Yet, technological innovation must align with faith-based and moral values to ensure that creativity contributes to ethical and sustainable learning outcomes. This study aims to explore how digital technology can be integrated with faith-based values to foster digital creativity and moral character among vocational students. Employing a mixed-method design, the research combined quantitative and qualitative approaches to capture both behavioral patterns and moral insights in students’ creative processes. The study involved 177 accounting students who produced digital projects such as multimedia presentations, videos, and graphic designs. Quantitative data were collected through documentation of these projects, while qualitative data were obtained through in-depth interviews with five students and two accounting teachers to understand how faith-based and moral values were embedded in digital creativity. Quantitative data were analyzed using descriptive statistics, and qualitative data were examined thematically using the Miles and Huberman interactive model. The findings revealed that Canva (139 students) and CapCut (142 students) were the most used applications, reflecting students’ preference for visual and multimedia-based creativity. Interviews indicated that values of responsibility, honesty, collaboration, and perseverance shaped their creative attitudes. An integrated analysis produced a four-component conceptual model: Input (digital technology), Process (project-based learning with faith values), Output (innovative products), and Outcome (creative, ethical, and sustainability-oriented learners). This study highlights how faith-driven digital creativity can balance technological mastery with moral integrity in achieving sustainable education.